2014
DOI: 10.1186/1471-2458-14-263
|View full text |Cite
|
Sign up to set email alerts
|

Q fever in the Netherlands: public perceptions and behavioral responses in three different epidemiological regions: a follow-up study

Abstract: BackgroundOver the past years, Q fever has become a major public health problem in the Netherlands, with a peak of 2,357 human cases in 2009. In the first instance, Q fever was mainly a local problem of one province with a high density of large dairy goat farms, but in 2009 an alarming increase of Q fever cases was observed in adjacent provinces. The aim of this study was to identify trends over time and regional differences in public perceptions and behaviors, as well as predictors of preventive behavior rega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…In accordance with this, we believe that the aforementioned modes of transmission were presented in the majority of patients in our study. Findings of other authors across European countries also confirmed these observations [45].…”
Section: Q Feversupporting
confidence: 73%
“…In accordance with this, we believe that the aforementioned modes of transmission were presented in the majority of patients in our study. Findings of other authors across European countries also confirmed these observations [45].…”
Section: Q Feversupporting
confidence: 73%
“…The second section was the “Standard questionnaire on risk perception of an infectious disease outbreak,” which was designed by the Municipal Public Health Service Rotterdam-Rijnmond, together with the National Institute for Public Health and the Environment in the Netherlands [ 32 ]. This tool was designed to study risk perceptions associated with the outbreak of infectious disease and has been used in many previous studies [ 33 , 34 ]. The generic questionnaire was tailored to address COVID-19 and was then translated into Arabic, which is the predominant language of the study sample in the chosen countries.…”
Section: Methodsmentioning
confidence: 99%
“…An outbreak in the Netherlands in 2007–2010 was thought to be associated with intensive dairy goat farming that reported an increased number of abortions in the years before the first human cases. ( 17 , 18 ) Cases were found to be residing within close proximity to the farms (5 km radius) that were thought to be the primary source of infection precipitated by the dry weather aerosolizing C. burnetti . ( 17 , 19 , 20 ) This demonstrates the necessity for surveillance and active case finding in the area surrounding an abattoir.…”
Section: Discussionmentioning
confidence: 99%
“…( 17 , 18 ) Cases were found to be residing within close proximity to the farms (5 km radius) that were thought to be the primary source of infection precipitated by the dry weather aerosolizing C. burnetti . ( 17 , 19 , 20 ) This demonstrates the necessity for surveillance and active case finding in the area surrounding an abattoir. It is important to note that only looking for symptomatic cases may grossly underestimate the number of exposures associated with an outbreak as was demonstrated by the Dutch experience.…”
Section: Discussionmentioning
confidence: 99%